The Best of Soccer Journal - An NSCAA guide to soccer coaching excellence (Meyer & Meyer Sport (UK) Ltd., 2012)
This book offers some of the best articles from the NSCAA's Soccer Journal from the last twenty years. Soccer Journal is the official publication of the National Soccer Coaches Association of America.